Assessment of flavor characteristics in snakehead (Ophiocephalus argus Cantor) surimi gels affected by atmospheric cold plasma treatment using GC-IMS - Huang, Jia-bao; Kong, Xian-wang; Chen, Ying-yun; Chen, Jing (Frontiers in Nutrition, 2023)
The gel formation ability of freshwater surimi is weak, resulting in poor flavor and quality, which hinders its application and development in surimi industry. Atmospheric cold plasma (ACP), a widely developed non-thermal processing technology in the food industry, has potential applications in maintaining and improving the flavor characteristics of surimi gels. In this study, the effect of atmospheric cold plasma on snakehead surimi gels flavor at different treatment times was investigated by GC-IMS. The experimental results of sensory evaluation showed that ACP could better maintain and improve the original appearance and tissue characteristics of surimi gels, scoring about 1-2 points higher than the control groups. In addition, 65 volatile organic compounds (VOCs) were also distinguished in surimi gels by GC-IMS, including aldehydes, alcohols, ketones, esters, and furans, to compare the difference in the volatile organic compounds composition between the sample groups. Specifically, the profiles of the ACP120 group was most unique and had the most obvious aroma characteristics in the processing groups, probably related to the highest thiobarbituric acid reactive substances values, reaching 73.28μmol MDA/kg sample. Meanwhile, the TCA-soluble peptides content was the lowest, indicating that ACP could promote the gel texture. In conclusion, ACP treatment can alter the flavor of surimi gels and provide new ideas for its application in food processing.